Fatal Outcome of Imatinib in a Patient with Idiopathic Hypereosinophilic Syndrome. (26th March 2018) - Abugroun, Ashraf; Chaudhary, Ahmed; Rodriguez, Gabriel
Abstract : Cytokine storm is a poorly explained clinical entity caused by an undesired and aggrandized immune system response leading to unregulated activation of the proinflammatory cascade, often contributing to multisystem organ failure and even death. Its potentially diverse etiologies and sepsis-like presentation have made it even more challenging to diagnose, and so far, no well-established treatment protocol has been proposed. Its association with certain medications, especially with monoclonal antibodies, has well been reported in literature. To the best of our knowledge, so far, no previous case of cytokine storm associated with imatinib has been reported. We herein present a case report of a 77-year-old male with a past medical history of hypereosinophilic syndrome who developed acute fatal cytokine storm following treatment with imatinib. This study highlights a life-threatening complication of the medication that may be underrecognized.